2000
DOI: 10.1029/1999jd901103
|View full text |Cite
|
Sign up to set email alerts
|

From model intercomparison toward benchmark UV spectra for six real atmospheric cases

Abstract: Abstract. The validity of a radiative transfer model can be checked either by comparing its results with measurements or with solutions for artificial cases. Unfortunately, neither type of comparison can guarantee that the spectral UV surface irradiance is accurately calculated for real atmospheric cases. There is a need therefore for benchmarks, i.e., standard results that can be used as a validation tool for UV radiation models. In this paper we give such benchmarks for six cloud-free situations. The chosen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 22 publications
(16 reference statements)
3
52
0
1
Order By: Relevance
“…The ratio of the modelled spectrum over the measured spectrum is shown in blue. Similar cloudless comparisions between measurement and model results have been presented by for example Forster et al (1995); Mayer et al (1997); Kylling et al (1998);Van Weele et al (2000) and Meloni et al (2003). The agreement between model simulation and measurement found here is comparable to that reported by those authors.…”
Section: Single Spectrum (Uvspec)supporting
confidence: 80%
See 2 more Smart Citations
“…The ratio of the modelled spectrum over the measured spectrum is shown in blue. Similar cloudless comparisions between measurement and model results have been presented by for example Forster et al (1995); Mayer et al (1997); Kylling et al (1998);Van Weele et al (2000) and Meloni et al (2003). The agreement between model simulation and measurement found here is comparable to that reported by those authors.…”
Section: Single Spectrum (Uvspec)supporting
confidence: 80%
“…Some of the above measurement versus model comparison papers also include model versus model comparisons (Van Weele et al, 2000;Bais et al, 2003;Hofzumahaus et al, 2004;Shetter et al, 2003). In addition to these the uvspec model has also successfully participated in a model comparison of UV-indices and the Intercomparison of 3-D Radiation Codes (Cahalan et al, 2005).…”
Section: Model Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences up to 14% in modelled UV were found between runs with estimated and climatic values of single scattering albedo (SSA), respectively. In four of the six benchmark cases considered by van Weele et al (2000) they found agreements against observed spectra within ±13% over the whole UV spectral region. These studies showed that model uncertainties are comparable with, but slightly larger than, measurement uncertainties.…”
mentioning
confidence: 92%
“…Several intercomparisons of UV models have been performed. Van Weele et al (2000) compared global and direct spectral UV calculations from 12 numerical models for six benchmark spectra corresponding to diverse conditions. They found agreements within ±3% for wavelengths longer than 320 nm and for high sun conditions.…”
mentioning
confidence: 99%